Peningkatan Kompetensi Manajemen Usaha Pada Siswa SMK Darul Hikmah Jurusan Tata Busana Melalui Pelatihan Penyusunan Business Plan - Astrian Kusumawati; Faqih Ulil Abshor; Sela Rachmawati; Putri Wulandari; Tiara Tiara (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to improve the business management competency of Darul Hikmah Vocational School Fashion Design students through business plan development training. The identified problem is the students' limited understanding of the aspects of structured business planning, despite their considerable technical skills in the fashion design field. The activity implementation method includes three stages: preparation, training implementation, and evaluation. The training was conducted business plan interactively through material delivery, case studies and group discussions, as well as hands-on practice in preparing a business plan. The results of the activity showed an increased understanding of the participants regarding the importance of structured business planning, business plan components, including market analysis, marketing strategy, financial planning, and operational management of a fashion business. Participants were able to prepare a simple, applicable business plan document in accordance with business potential in the fashion industry. This activity is expected to provide provisions for students to be able to become independent entrepreneurs after graduating from vocational high school.